1994
DOI: 10.1007/bf01279520
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' and students' views and attitudes towards a new mathematics curriculum: A case study

Abstract: ABSTRACT. The education system in Portugal is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
3

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 11 publications
2
15
0
3
Order By: Relevance
“…It may be the case that, similar to that which was reported by Ponte et al (1994), the Project Maths curriculum is being embraced in a more comprehensive manner by younger secondary school students, thus the effects of this change would not be evident at Leaving Certificate or upon their entry to third level education for a number of years. Research has shown that mathematics curriculum reform takes time to fully implement with plenty of obstacles impeding widespread adoption of the ideals espoused (Handal and Herrington 2003;Schoenfeld 2014).…”
Section: Analysing the Impact Of Mathematics Curriculum Changementioning
confidence: 84%
See 2 more Smart Citations
“…It may be the case that, similar to that which was reported by Ponte et al (1994), the Project Maths curriculum is being embraced in a more comprehensive manner by younger secondary school students, thus the effects of this change would not be evident at Leaving Certificate or upon their entry to third level education for a number of years. Research has shown that mathematics curriculum reform takes time to fully implement with plenty of obstacles impeding widespread adoption of the ideals espoused (Handal and Herrington 2003;Schoenfeld 2014).…”
Section: Analysing the Impact Of Mathematics Curriculum Changementioning
confidence: 84%
“…However, passing judgement at this point regarding the overall impact of the recently introduced Project Maths curriculum would be premature. Portugal implemented a mathematics curriculum change at secondary level in the early 1990s which was quite similar to the mathematics curriculum change implemented in Ireland recently as greater emphasis was placed on problem-solving, real world applications, and graphical representations (Ponte et al 1994). Ponte et al (1994) completed a comprehensive study of the views and attitudes of teachers and students who were involved in a pilot curriculum development programme for this curriculum change.…”
Section: Analysing the Impact Of Mathematics Curriculum Changementioning
confidence: 99%
See 1 more Smart Citation
“…Another important point to mention is that students may depend only on the given model or visual material or device (Ponte, Matos, Guimar, Leal and Canavarro, 1994) instead of the knowledge that is aimed to be learnt. It is necessary for students to understand the relationship between the symbolic form of the mathematical notion and its visual representation (Viholainen, 2008).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…An interesting contribution is given by Ponte et al (1994), when discussing a new type of professional knowledge for mathematics teachers. They support the idea of blending of mathematical content with pedagogical knowledge: in their view such blending has to draw on different components of current knowledge to produce a restructuring of the teachers craft knowledge.…”
Section: Didactics Of Mathematics and School Practicementioning
confidence: 99%